Synthesis and Spectral Characterization of a Unsymmetrical Ligand, N,N’-Bis(4-fluorobenzylidene)propane-1,2-diamine and Its Zinc Complexes - JOOHARI, SHIVA; MONTAZEROZOHORI, MORTEZA; ALIREZA MUSAVI, SAYED (Asian Journal of Chemistry, 2010)
A new unsymmetrical bidentate Schiff base ligand i.e., N,N'-bis(4- fluorobenzylidene)propane-1,2-diamine (BFBPD) was synthesized. Four zinc complexes of this ligand with general formula of Zn(BFBPD)X2 in which X is Cl–, Br–, I– or SCN–, have been prepared. The ligand and its complexes were characterized by elemental analyses, MS, 1H NMR, 13C NMR, FT-IR and UV spectra and molar conductance. All compounds were found to be non-electrolytes in the DMF solutions.